Construcción de un diagrama de Hubble: Una herramienta para la Enseñanza de la Astronomía - Cardona-Rodriguez, Giovanni; Reyes- Roncancio, Jaime Duván; Giraldo, Mauricio (Revista Científica, 2016)
This article presents the construction and analysis of an activity that can support the work of teachers who run Astronomy clubs and want to address the issue of evolution of the Universe. Here Hubble's law is reconstructed by reproducing a Hubble diagram with Sloan Digital Sky Survey's (SDSS) data, from which the Hubble parameter value is obtained and the expansion of the Universe is inferred. This educational activity allows teachers to guide their students along the path followed by Hubble to determine his law. In this sense some implications of applying the latter are discussed in the context of teacher's training in Physics and Astronomy clubs.